2019
DOI: 10.1093/aob/mcz160
|View full text |Cite
|
Sign up to set email alerts
|

The SAUR41 subfamily of SMALL AUXIN UP RNA genes is abscisic acid inducible to modulate cell expansion and salt tolerance in Arabidopsis thaliana seedlings

Abstract: Background and Aims Most primary auxin response genes are classified into three families: AUX/IAA, GH3 and SAUR genes. Few studies have been conducted on Arabidopsis thaliana SAUR genes, possibly due to genetic redundancy among different subfamily members. Data mining on arabidopsis transcriptional profiles indicates that the SAUR41 subfamily members of SMALL AUXIN UP RNA genes are, strikingly, induced by an inhibitory phytohormone, abscisic acid (ABA). We aimed to reveal the physiological ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 63 publications
5
56
0
Order By: Relevance
“…Thus, we generated saur41/40/71/72 quadruple mutants using the CRISPR/Cas9 (Clustered Regulatory Interspaced Short Palindromic Repeats/CRISPR Associated Protein 9) genome editing technique. 5 As expected, by a quantitative real-time PCR analysis, we found that the Arabidopsis SAUR41 subfamily genes were activated by ABA but not by gibberellic acids (GA) and BR. 5 Here, the ABA sensitivity of the three genotypes, the saur41/40/71/72 quadruple mutants, the SAUR41 overexpression lines (OE-SAUR41), and the wild-type (Col-0), was tested by sowing the seeds of same age on low concentrations (0-0.75 μM) of exogenous ABA.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…Thus, we generated saur41/40/71/72 quadruple mutants using the CRISPR/Cas9 (Clustered Regulatory Interspaced Short Palindromic Repeats/CRISPR Associated Protein 9) genome editing technique. 5 As expected, by a quantitative real-time PCR analysis, we found that the Arabidopsis SAUR41 subfamily genes were activated by ABA but not by gibberellic acids (GA) and BR. 5 Here, the ABA sensitivity of the three genotypes, the saur41/40/71/72 quadruple mutants, the SAUR41 overexpression lines (OE-SAUR41), and the wild-type (Col-0), was tested by sowing the seeds of same age on low concentrations (0-0.75 μM) of exogenous ABA.…”
supporting
confidence: 76%
“…5 As expected, by a quantitative real-time PCR analysis, we found that the Arabidopsis SAUR41 subfamily genes were activated by ABA but not by gibberellic acids (GA) and BR. 5 Here, the ABA sensitivity of the three genotypes, the saur41/40/71/72 quadruple mutants, the SAUR41 overexpression lines (OE-SAUR41), and the wild-type (Col-0), was tested by sowing the seeds of same age on low concentrations (0-0.75 μM) of exogenous ABA. The ABA concentrations used here were unable to block Arabidopsis seed germination, but reduced the cotyledon greening/expansion rate in a dose-dependent manner.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Also, several genes involved in cell wall organization such as the pectin lyase At2g43890, the pectin methylesterase ATPM EI11 and the expansin EXP17 showed a large high pH /low pH ratio, possibly to compensate compromised cell expansion at alkaline pH. This supposition is supported by a large high pH/low pH ratio of the auxin-related genes SAUR41 and SAUR72, which have been associated with the regulation of cell expansion [13,18]. High pH /low pH ratios below one were observed for STRESS INDUCED FACTOR1 (SIF1), a root-specific, membraneanchored LRR kinase with undefined function [33], the aluminum-activated malate transporter ALMT1, and the Cys2-His2 zinc-finger domain transcription factor SEN-SITIVE TO PROTON RHIZOTOXICITY 2 (STOP2).…”
Section: Ambient Ph Modulates the Iron Deficiency Responsementioning
confidence: 95%